Health care staff ’ perceptions of a career in family medicine - Waeul Hussin Alsaleh,; Maali Mansoor Buamer,; Zahra Abdullah Taha Alsafi,; Saeed Mohammed Saeed Alelyani,; Ranya Abdullah Hamza Bajuo,; Haneen Saad Aljohani,; Afaq Alfaraj, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background:The choice of medical specialty is a critical decision for Health care staff, influenced by various factors such as lifestyle preferences, professional aspirations, and job satisfaction. Despite the strong link between robust primary care systems and improved health outcomes, many countries face a shortage of primary care physicians. This shortage is exacerbated by an aging healthcare workforce and declining interest in primary care specialties among Health care staff . Understanding the factors that influence specialty choice is essential for addressing these shortages and promoting primary care careers. Methods:This study targeted final-year Health care staff from two medical schools, using a questionnaire designed to explore the factors influencing specialty choice. The study employed a marketing research framework, examining both the selection criteria of Health care staff and their perceptions of different specialties. The questionnaire covered topics such as interest in 19 medical specialties, the importance of 25 selection criteria, and perceptions of six core specialties, including family medicine. The responses were analyzed using chi-square tests, frequency distributions, and t-tests, with statistical significance set at p<0.05. Results:The study achieved a 66% response rate, with 218 Health care staff participating. Of these, 19% expressed interest in family medicine (FM). Female Health care staff showed a higher inclination toward FM (68% vs. 32%; P=0.025). Health care staff interested in FM favored specialties with bedside care, long-term patient relationships, a controllable lifestyle, and daytime hours. While Health care staff not interested in FM shared some similar lifestyle preferences, they perceived FM as less intellectually stimulating and lower in prestige. Furthermore, 26% of FM-interested Health care staff and 14% of non-interested Health care staff perceived FM as being in crisis, though this difference was not statistically significant. Conclusion:The findings suggest that family medicine's appeal lies in its perceived work-life balance, patient relationships, and manageable hours, yet it suffers from perceptions of low prestige and limited academic opportunities. To attract more Health care staff to family medicine, efforts should focus on improving its reputation, highlighting its lifestyle benefits, and providing positive exposure during medical education. Addressing these perceptions could help alleviate the primary care workforce shortage and strengthen healthcare systems.